Coffee consumption rapidly reduces background DNA strand breaks in healthy humans: Results of a short‐term repeated uptake intervention study. Issue 3 (29th December 2015) - Bakuradze, Tamara; Lang, Roman; Hofmann, Thomas; Schipp, Dorothea; Galan, Jens; Eisenbrand, Gerhard; Richling, Elke
Abstract : The long‐term consumption of coffee is associated with improved DNA integrity in healthy volunteers. To test whether these effects could be shown after acute and repeated coffee consumption within a day, a short‐term study was performed. The results demonstrate that the intake of coffee within hours significantly reduced background DNA strand breaks, measured by comet assay. Abstract : Scope: Intervention studies provide evidence that long‐term coffee consumption correlates with reduced DNA background damage in healthy volunteers. Here, we report on short‐term kinetics of this effect, showing a rapid onset after normal coffee intake. Methods and results: In a short‐term human intervention study, we determined the effects of coffee intake on DNA integrity during 8 h. Healthy male subjects ingested coffee in 200 mL aliquots every second hour up to a total volume of 800 mL. Blood samples were taken at baseline, immediately before the first coffee intake and subsequently every 2 h, prior to the respective coffee intake. DNA integrity was assayed by the comet assay. The results show a significant ( p < 0.05) reduction of background DNA strand breaks already 2 h after the first coffee intake. Continued coffee intake was associated with further decrements in background DNA damage within the 8 h intervention ( p < 0.01 and p < 0.001, respectively). Mean tail intensities (TIs%) decreased from 0.33 TI% (baseline, 0 h) to 0.22 TI% (within 8 h coffee consumption). Conclusion: Repeated coffee consumption was associated with reduced background DNA strand breakage, clearly measurable as early as 2 h after first intake resulting in a cumulative overall reduction by about one‐third of the baseline value.